PROBLEMS OF SYSTEMS WITH DISTRIBUTED GENERATION - TSYPLENKOV, Dmytro; SUVORKIN, Olexsandr (My University, 2018)
The problems of the development of modern production are related to the demand for electricity, which is ahead of the increase in generating capacity. Electric power industry in the 20 th century developed mainly by increasing the level of centralization of electricity supply in the creation of ever more powerful electric power facilities.
Keywords: distributed generation renewable energy sources; power quality